Menimbang Gagasan Islamisasi Ilmu-ilmu Sosial; Studi Kritis atas Pemikiran Ismail Raji Al-Faruqi - Muhyidin Muhyidin; Dewi Mutmainnah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
The idea of Islamization of knowledge in essence emerged as a response to the dichotomy between religious science and science that the secular West and modern culture introduced into the Islamic world. The progress achieved by modern science has had an amazing effect, but on the other hand it has also had a negative impact, because modern (Western) science has dry values or is separated from religious values. In addition, the Islamization of Science is also a reaction to the crisis in the education system faced by Muslims, namely the dualism of the Islamic education system and modern (secular) education which confuses Muslims. According to Al-Faruqi, Islamization is an effort to understand and rebuild social and natural sciences in which there are Islamic elements, so that they change to be in line with Islamic orientation. And every scientific discipline must cultivate Islamic principles whose methodology is imbued with the spirit of monotheism, which includes: the principle of the oneness of God, the unity of the universe, the unity of truth and knowledge, the unity of life, and the unity of mankind